Establishing premises for inter-professional collaborative practice in school: inclusion, difference and influence. Issue 20 (25th September 2021) - Gallagher, A. L.; Murphy, C. A.; Conway, P. F.; Perry, A.
Abstract: Purpose: To ascertain stakeholders' agreement and disagreement about inter-professional collaboration (IPC) when supporting the child with a developmental language disorder (DLD) in school. Materials and methods: Two rounds of an online Delphi survey were undertaken with a purposive sample of 26 participants (researchers, practitioners and parents). Topics were informed by the views of children engaged in an earlier phase of the research. Agreement was set at an inter-quartile range of 1, with level of agreement measured using a five-point semantic differential scale. Qualitative data were examined using content analysis. Results: There was strong agreement across the stakeholder groups about the child-led goals of IPC. Stakeholders also agreed that DLD is best viewed as a learning difference rather than a disorder. We identified ambivalence across the groups about the right of the child with DLD to have influence in decision-making about supports in school. Conclusions: We propose that IPC should be viewed as a means of ensuring the inclusion of the child in school. A shift in focus from remediating perceived deficits of the child, to affecting change in classroom practice, is also indicated. The need to reinforce the unconditional right of the child to have influence in decisions about supports is highlighted. Implications for IPC when meeting the needs of children with a developmental disability in school are outlined. IMPLICATIONS FOR REHABILITATION: The goal of inter-professional collaboration should be to ensure the inclusion of the child with a developmental disability in school. Interventions delivered in school should focus on changing practice in the classroom, rather than on the child's perceived deficits. The child with a developmental disability should be given influence in collaborative decision-making to ensure supports are relevant and responsive to their needs.